2023
DOI: 10.1002/lno.12452
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Extratropical Cyclone Fiona on a sensitive coastal lagoon ecosystem

Abigail C. Bonnington,
Rob C. Jamieson,
Kathryn A. Smith
et al.

Abstract: Oceanic storms can strongly disturb the physical and biogeochemical conditions of transitional coastal waters. Impacts of extreme oceanic storms on coastal ecosystems have received limited attention worldwide, with no studies at higher latitudes (> 45°) where tropical cyclones have usually abated. This study investigates the combined impacts from marine and atmospheric forcing on a coastal lagoon in Prince Edward Island, Canada, during and after Extratropical Cyclone Fiona in September 2022. Physical (water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Also, it is possible that the springs throughout the watershed (Figure S1) exhibit spatiotemporal variability in NO 3 -N concentrations not captured in the sporadic sampling reported here (Table 1). For example, extreme rainfall events have been shown to drive sustained increases in NO 3 -N levels in the Basin Head tributaries (Bonnington et al, 2023). However, this study was conducted during the baseflow season when This finding is consistent with other studies which reported that SGD can deliver a comparable (or sometimes higher) chemical load to coastal waters than rivers (Kim et al, 2003;Lecher et al, 2015;Lee et al, 2009;Santos et al, 2021;Slomp & Van Cappellen, 2004), even though SGD is rarely monitored.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Also, it is possible that the springs throughout the watershed (Figure S1) exhibit spatiotemporal variability in NO 3 -N concentrations not captured in the sporadic sampling reported here (Table 1). For example, extreme rainfall events have been shown to drive sustained increases in NO 3 -N levels in the Basin Head tributaries (Bonnington et al, 2023). However, this study was conducted during the baseflow season when This finding is consistent with other studies which reported that SGD can deliver a comparable (or sometimes higher) chemical load to coastal waters than rivers (Kim et al, 2003;Lecher et al, 2015;Lee et al, 2009;Santos et al, 2021;Slomp & Van Cappellen, 2004), even though SGD is rarely monitored.…”
Section: Discussionsupporting
confidence: 88%
“…The shallow (mostly <2 m deep) lagoon experiences a mixed semi-diurnal tide with a 0.8 m and 1.3 m tidal range at spring and neap tides, respectively, and a mean residence time of 2-7 days (Sharp et al, 2003). Tidal pumping occurs through a narrow channel (Figure 1), making the lagoon vulnerable to ecosystem disturbances from storm-surge-driven mixing during hurricanes and other coastal storms (Bonnington et al, 2023).…”
Section: Study Sitementioning
confidence: 99%
“…Extreme value analysis (Figure S2b in Supporting Information S1; Kamphuis, 2020) on 65 years of hindcast wave data for the modeled location revealed that the maximum significant wave heights observed during this storm have a relatively short return period (<3 years). However, water levels from the combined effect of waves and storm surge made this a historic event, significantly impacting coastal developments and ecosystems in PEI (e.g., Bonnington et al, 2023). Satellite imagery from Planet Team (2017) and images from the COASTIE citizen science program (coastiecanada.ca) revealed intensive beach/dune erosion and sediment transport (Figure 3b).…”
Section: Landfall Of Hurricane Fiona In Atlantic Canadamentioning
confidence: 99%